A Monetary Policy Model Without Money for India - Kapur, Muneesh; Patra, Michael (Washington, D.C. : International Monetary Fund, 2010)
A New Keynesian model estimated for India yields valuable insights. Aggregate demand reacts to interest rate changes with a lag of at least three quarters, with inflation taking seven quarters to respond. Inflation is inertial and persistent when it sets in, irrespective of the source. Exchange rate pass-through to domestic inflation is low. Inflation turns out to be the dominant focus of monetary policy, accompanied by a strong commitment to the stabilization of output. Recent policy actions have raised the effective policy rate, but the estimated neutral policy rate suggests some further tightening to normalize the policy stance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet